The Use of Facebook for Senior Learners of English as a Second Language - Margareth Jane Tanos (Syntax Corporation, 2023)
Social media, which reaches the world, is believed to be an informal method of learning the English language. As 56.8% of the world's population is active on social media, which equals approximately 4.47 billion persons, this could be a large and wide possibility to be an English language learning platform. The method chosen to conduct this research is qualitative using discourse analysis, where a group of fifteen seniors aged 40-60 years old, with high school education levels residing in Manado, North Sulawesi, and surrounding areas were selected as participants. The participants were asked to fill out questionnaires and interviews regarding their use of Facebook and WhatsApp and their interest in the use of English while using social media. The findings of the study showed that participants used social media mainly for expressive types of speech acts such as greetings, apologies, and congratulations. The participants also tended to use the features of social media that allowed them to express emotions mostly in pictograms, with an English word of expression, pictures, and emoticons. In addition, the plurilingual practice was also observed in the use of mixed codes which served to enhance the mutual understanding and interactions among the participants.